(untitled) (Annals of Medical Research, 2021)
Aim: In the treatment of vertebral compression fractures, kyphoplasty stands out as an effective treatment method that has been performed more frequently in recent years. The etiology of compression fractures varies from patient to patient. Biopsy results taken from the patients during the procedure reflect these differences. We wanted to emphasize the importance of the biopsy procedure performed during kyphoplasty by evaluating the biopsy results.Materials and Methods: The patient files, radiological images and biopsy results of the patients, who were treated with kyphoplasty due to vertebral compression fracture and who had a biopsy performed during this procedure between 2017 and 2019. Results: The total number of operated patients was found to be 201, and the number of vertebrae biopsies was 269. Eighty-three of our patients were male and 118 were female. Of the 269 biopsy results in total, 18 (6.7%) had pathological findings; 3 of them were compatible with osteomyelitis, while the remaining 15 were malignant.Conclusion: Since the biopsy procedure performed during the treatment of vertebral compression fractures with kyphoplasty could be performed safely and provides an opportunity for early diagnosis and treatment, a biopsy requirement for the benefit of patients would be inevitable in all kyphoplasty procedures.